Metabolic Syndrome Induced by Hipercalory Diet in Wistar Rats: impact on diabetic risk, dyslipidemia and hypertension complication - Dimas Thoriq Muhammad Iqbal; Fadlina Chany Saputri; Abdul Mun’im; Vicko Suswidiantoro (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Objective: Metabolic syndrome is a group of metabolic disorders that are usually found in individuals with a high risk of type 2 diabetes mellitus (T2DM) and cardiovascular disease. Comparison of diet composition, especially macronutrients, over a certainperiode in both humans and experimental animals can allegedly increase the risk of metabolic syndrome. This study aims to determine the use of a hypercaloric diet that can cause metabolic syndrome in male Wistar rats. Methods: The hypercaloric diet was administered orally in pellets and oral solution to rats for 16 weeks. Analysis of the condition of the metabolic syndrome was carried out by looking at the increase in serum levels of total cholesterol, triglycerides and decreased HDL levels. Fasting blood sugar and fasting insulin levels were also seen to increase and blood pressure testing was carried out to see an increase in blood pressure after 16 weeks of giving a hypercaloric diet. Results: Administration of a hypercaloric diet showed an increased risk of metabolic syndrome in rats. Administration for 16 weeks showed a significant difference in the improvementofs conditions of dyslipidemia, insulin resistance and hypertension. Conclusion: Based on the results, a hypercaloric diet for 16 weeks can cause metabolic syndrome in rats. Abstrak: Objektif: Sindrom metabolik adalah sekelompok kelainan metabolik yang biasanya ditemukan pada individu dengan risiko tinggi diabetes militus tipe 2 (T2DM) dan penyakit kardiovaskular. Perbandingan komposisi diet khususnya makronutrien, dalam jangka waktu tertentu baik pada manusia maupun hewan coba disinyalir dapat meningkatkan resiko dari sindroma metabolik. Penelitian ini bertujuan untuk menentukan penggunaan diet hipercalori yang dapat menyebabkan kondisi sindrome metabolikpada tikus Wistar jantan. Metode:diet hiperkalori diberikan secara oral dalam bentuk pelet dan larutan oral pada tikus selama 16 minggu. Analisis terhadap kondisi syndrome metabolic dilakukan dengan melihat peningkatan kadar serum kolesterol total, trigliserida dan penurunan kadar HDL. Kadar gula darah puasa dan insulin puasa juga dilihat peningkatannya serta dilakukan pengujian tekanan darah untuk melihat terjadinya peningkatan tekanan darah setelah 16 minggu pemberian diet hiperkalori. Hasil: Pemberian diet hiperkalori menunjukkan adanya peningkatan risiko sindrom metabolic pada tikus. Pemberian selama 16 minggu menujukkan adanya perbedaan signifikan pada peningkatan kearah kondisi dyslipidemia, resistensi insulin dan hipertensi. Kesimpulan: Berdasarkan hasil, pemberian diet hiperkalori  selama 16 minggu dapat menyebabkan terjadinya kondisi sindrom metabolic pada tikus